The control of the economy - STEINDL, J. (PSL Quarterly Review, 2013)
The control of the economy is examined in terms of the relationships between instruments and targets. The endogeneity of the budget deficit is analysed, exploring 'reflation' as a possible solution, and it is shown that monetarism has changed people's response patterns. The mechanical approach to economic management, and particularly inflation, is rejected in favour of political solutions and long-term planning. JEL: E43, E52